2003
DOI: 10.1046/j.1365-2850.2003.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring sexual and relationship possibilities for people with psychosis – a review of the literature

Abstract: This review examines the literature on sex and relationship issues in the context of serious and persistent mental health problems. It identifies gaps in the research and highlights key issues needing further investigation. The available published documents have been identified, which contain information, ideas, data and evidence on the topic. A critical analysis of the subject, through the examination of the various documents, is provided. The main themes that emerged included HIV/AIDS, medication and sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 81 publications
4
59
0
Order By: Relevance
“…Participants' informal responses suggested that most were interested in a romantic relationship, but did not have one. These findings are similar to earlier reports (Deegan 2001;Geiger et al 2005;McCann 2000McCann , 2003Padget et al 2008;Wright et al 2007) demonstrating difficulties involved in forming and maintaining intimate/ romantic relationships. Possible explanations relating to the difficulties involved in having romantic relationships can be found in the few studies that attempted to investigate the experience of love and intimate relations among consumers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Participants' informal responses suggested that most were interested in a romantic relationship, but did not have one. These findings are similar to earlier reports (Deegan 2001;Geiger et al 2005;McCann 2000McCann , 2003Padget et al 2008;Wright et al 2007) demonstrating difficulties involved in forming and maintaining intimate/ romantic relationships. Possible explanations relating to the difficulties involved in having romantic relationships can be found in the few studies that attempted to investigate the experience of love and intimate relations among consumers.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to these are the fear of a romantic relationship's potential damage to the therapeutic process (Wright et al 2007) and rigidity in the rules of the institutions that provide care (Deegan 2001;Geiger et al 2005;McCann 2000;Wright et al 2007). Also contributing to these difficultites are inadequate social skills for maintaining romantic relationships (Geiger et al 2005;Wright et al 2007), stigma (Deegan 2001;Geiger et al 2005;McCann 2003;Wright et al 2007) self-stigma, difficulty in sexual functioning (Deegan 2001;Wright et al 2007), difficulty in finding partners (McCann 2000;Wright et al 2007) and the availability of potential partners (Wright et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have emerged in the limited research in mental health (McCann, 2003;Quinn et al, 2011a) and other health care settings (Hordern, 2008;Katz, 2005;Kotronoulas et al, 2009). Perceived issues around gender and professional boundaries were not found in these other settings, suggesting that these may be specific mental health issues presenting additional barriers.…”
Section: Discussionsupporting
confidence: 77%
“…The 5-As for including sexual concerns in practice, identifies Avoidance as the participants' original practice relating to sexual health concerns (McCann, 2003;Quinn et al, 2011a). Awareness-building occurs through the provision of specific education on sexual health concerns for consumers, such as sexual safety, sexual abuse and exploitation, sexual vulnerability, and sexual function problems associated with medication along with the effects illness and symptoms can have upon sexual response and sexual confidence (Cort et al, 2001;Krebs, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested (Magnan, Reynolds, & Galvin, 2005;McCann, 2003;Quinn et al, in press) that nurses avoid sexuality topics with consumers for reasons of personal embarrassment, that the topic is not important, or is someone else's responsibility. The evidence here suggests that avoidance may reflect the fear that talking about sexuality might be viewed by fellow nurses as a boundary violation.…”
Section: Discussionmentioning
confidence: 99%